PENGARUH INSTAGRAM MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP MINAT BERKUNJUNG DI KINARA SUNSET TANJUNG BIAS BEACH - Marisa Saopi Yanti; Rusminah HS; Emilia Septiani (Distribusi - Journal of Management and Business, 2022)
This study aims to determine the effect of Instagram marketing and electronic word of mouth on the interest to visit Kinara Sunset Tanjung Bias beach, the method of the research used is associative. Population in this study are people who live in Mataram and West Lombok and have been knows Kinara Sunset but never visited.The method used is asumple survey method with data proscribed a google form quisioner and sample of this study were 100 respondents and the sampling technique used non-probability sampling methods. The analysis used multiple linear regression analysis. Data analysis technique using the SPSS version 25 program. The results of the analysis for the Instagram Marketing variable a positive and significant effect on Interest to Visit Kinara Sunset, while the Electronic Word Of Mouth is so that it has a positive significant effect on Interest to Visit Kinara Sunset. The coefficient of has positive and significant effect on Interest to Visit Kinara Sunset.